Glycosylation of MUC6 by α1, 4‐linked N‐acetylglucosamine enhances suppression of pancreatic cancer malignancy. Issue 2 (28th November 2021) - Yuki, Atsuko; Fujii, Chifumi; Yamanoi, Kazuhiro; Matoba, Hisanori; Harumiya, Satoru; Kawakubo, Masatomo; Nakayama, Jun
Abstract: Biomarkers for early diagnosis of pancreatic cancer are greatly needed, as the high fatality of this cancer is in part due to delayed detection. α1, 4‐linked N ‐acetylglucosamine (αGlcNAc), a unique O ‐glycan specific to gastric gland mucus, is biosynthesized by α1, 4‐ N ‐acetylglucosaminyltransferase (α4GnT) and primarily bound at the terminal glycosylated residue to scaffold protein MUC6. We previously reported that αGlcNAc expression decreases at early stages of neoplastic pancreatic lesions, followed by decreased MUC6 expression, although functional effects of these outcomes were unknown. Here, we ectopically expressed α4GnT, the αGlcNAc biosynthetic enzyme, together with MUC6 in the human pancreatic cancer cell lines MIA PaCa‐2 and PANC‐1, neither of which expresses α4GnT and MUC6. We observed significantly suppressed proliferation in both lines following coexpression of α4GnT and MUC6. Moreover, cellular motility decreased following MUC6 ectopic expression, an effect enhanced by cotransduction with α4GnT. MUC6 expression also attenuated invasiveness of both lines relative to controls, and this effect was also enhanced by additional α4GnT expression. We found αGlcNAc‐bound MUC6 formed a complex with trefoil factor 2. Furthermore, analysis of survival curves of patients with pancreatic ductal adenocarcinoma using a gene expression database showed that samples marked by higher A4GNT or MUC6 mRNA levels were associated with relatively favorable prognosis. These results strongly suggest that αGlcNAc and MUC6 function as tumor suppressors in pancreatic cancer and that decreased expression of both may serve as a biomarker of tumor progression to pancreatic cancer. Abstract : In this study, we demonstrated tumor‐suppressive effect of ectopic MUC6 expression and α1, 4‐linked N ‐acetylglucosamine (αGlcNAc) binding to MUC6 on two pancreatic cancer cell lines. We also showed that the cases with higher expression levels of A4GNT encoding α1, 4‐ N ‐acetylglucosaminyltransferase, which catalyzes biosynthesis of αGlcNAc and MUC6 transcript, had a preferable prognosis of pancreatic ductal adenocarcinoma patients. These results indicate that αGlcNAc and MUC6 function as tumor suppressors in pancreatic cancer and that decreased expression of αGlcNAc and MUC6 may be useful biomarkers for the initiation of tumor progression to pancreatic cancer.